PEMANFAATAN FOTO UDARA DIGITAL INFRAMERAH BERWARNA FORMAT KECIL DARI WAHANA BALON UDARA UNTUK PEMETAAN KERUSAKAN TANAMAN PADI (ORYZA SATIVA) AKIBAT SERANGAN HAMA TIKUS SAWAH (RATTUS ARGENTIVENTER) - , WIKAN JAYA P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to explore the capability of digital false color small format aerial photograph that flown using simple balloon as a data for rice plant (Oryza sativa) damage mapping, especially due to the rat (Rattus argentiventer) raid. The second goal is to build the interpretation key for damage identification of rice plant using false color small format aerial photograph. The research area controlled in the some extent of rice field that has a rice plant damage variation due to the rat raid. Researcher using a false color modified camera to capture those phenomenon. A number of helium balloons also used as a platform to flown it up. Resulted image quality tested in some aspects